Legal Protection Concerning Children Facing Economic Exploitation in Batam City - Tan, Winsherly; Tan, David; Rahmadani, Aini (Fakultas Hukum, Universitas Islam Balitar, 2024)
The arbitrary economic exploitation of children by parents and other interested parties requires immediate attention. Batam City, located in the Riau Archipelago, is known for its innovation and low crime rates, primarily due to its focus on foreign relations. However, despite these positive aspects, the economic exploitation of children remains a significant issue, with economic factors playing a crucial role. This study aims to investigate the legal protection of children as victims of economic exploitation in Batam City using an empirical legal research method. This approach involves analyzing and examining the functioning of law within society, utilizing both primary and secondary data sources. The objective is to analyze legal protection for children as victims of economic exploitation from the perspectives of justice, utility, and legal certainty. The findings confirm that legal regulations concerning the protection of children from economic exploitation are clearly stipulated in the law. Various legal protection measures are available for children who fall victim to exploitation. However, enhancing parental awareness is essential to ensure consistent attention to the rights and obligations owed to their children.